Wierzenia i obrzędy plemienne źródłemreligiologicznych inspiracji –. rozważania na podstawie myśli teologicznejks. prof. Tadeusza Dajczera - Kaczmarek, Piotr (Warszawskie Studia Teologiczne, 2019)
Human existence comprises of both the vertical and the horizontal dimensions. The former opens the human being to the supernatural, while the latter is of no less significance for the peoples of primitive religions. Primary cultures discovered their identity in the cosmic dimension. This was connected with special initiation rites that opened man to the reality of the sacred. Fr. Tadeusz Dajczer devoted much of his scientific research to the study of beliefs and rites of primitive religions, especially those cultivated among North American Indians. The role of myth has been made closer for a better understanding of the issues discussed, through which, its symbolism, introduces man into the subjective dimension of reality. A very important thing to note is the agrarian revolution that took place during the Neolithic period. Thanks to this, it gave human societies a more settled way of life. This helped in the observation of nature and its natural cycles of birth and death. In turn, it made people aware that they live in a time of constant repetition of cycles. The guiding thought is the motivation of life and vitality, in which the man of primitive religions tried to incorporate by special rites of initiation.